Lyotropic mesomorphism and morphology in non-aqueous solutions of three tetranuclear platinum mesogens with different halogen-bridged groups - Nesrullajev, A; Bilgin-Eran, B; Kazanci, N (ELSEVIER SCIENCE SA, 2002)
The lyotropic mesomorphism and morphological properties of anew type of lyotropic liquid crystalline system, i.e. a tetranuclear platinum mesogen/apolar organic solvent, have been investigated. The texture transformations in a large temperature interval, especially in the phase transition regions have been studied. The temperature widths of the heterophase regions of the nematic-nematic and nematic-isotropic liquid phase transitions have been determined with a high accuracy. (C) 2002 Published by Elsevier Science B.V.
Keywords: lyotropic mesomorphism; tetranuclear platinum mesogens; nematic-nematic liquid phase transition; nematic-isotropic liquid phase transition; APOLAR ORGANIC-SOLVENTS; PALLADIUM ORGANYLS; NEMATIC MESOPHASES; LIQUID-CRYSTALS; DI-PALLADIUM; BEHAVIOR; COMPLEX; Materials Science